Impact of sensorimotor mismatch on virtual reality sickness and user experience: age-related differences in a randomized trial - Elisabeth Jochmann; Thomas Jochmann; Maximilian Weber; Karolin Weigel; Carsten Klingner (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Virtual reality (VR) technology offers immersive and interactive experiences and is increasingly being explored for rehabilitation therapies. However, concerns about side effects such as nausea and dizziness—collectively referred to as VR sickness—are holding back clinical translation. Sensorimotor mismatches, while potentially beneficial for motor learning, may exacerbate these effects. The age groups in VR applications differ, with younger users common in gaming and older adults prevalent in rehabilitation. This study investigated whether sensorimotor mismatches in a VR-based motor task make the experience more uncomfortable and whether older adults are more affected by these mismatches. Methods We conducted a randomized controlled trial with 104 healthy right-handed adults, including elderly participants up to 84 years old, to cover the relevant demographics for rehabilitation. Participants were divided into three intervention groups and performed a VR ball-throwing task using an Oculus Rift S head-mounted display. The groups differed in task difficulty and exposure to deliberately induced sensorimotor mismatches. The design avoided visual-vestibular conflicts typically responsible for VR sickness and instead introduced proprioceptive mismatches during hand-object interaction. VR sickness was measured using the Simulator Sickness Questionnaire (SSQ), and user experience was assessed through a self-developed questionnaire. Statistical analysis was performed using rank-transformed ANOVA, ordinal logistic regression, and Spearman’s rho with FDR correction for multiple comparisons. Results Results indicated no significant differences in SSQ scores among the three intervention groups, suggesting that sensorimotor mismatches do not increase VR sickness. However, the Mismatch group reported higher levels of exhaustion and frustration compared to the Error-based and Errorless groups, indicating the impact of cognitive strain and task difficulty on user experience. Interestingly, younger participants reported higher (worse) SSQ scores, while older participants experienced weaker symptoms. Conclusions VR environments with sensorimotor mismatches during hand-object interaction tasks may be feasible for rehabilitation, as they did not lead to significant discomfort in this setting. Moreover, despite concerns about age-related susceptibility to dizziness, older adults showed high tolerance to VR, supporting its potential for broader applications in rehabilitation settings. This study was reported in accordance with the CONSORT guidelines. It was registered in the German Clinical Trials Register (DRKS00034901).